Drug Dependence, Synaptic Plasticity, and Tissue Plasminogen Activator - Kiyofumi Yamada; Taku Nagai; Toshitaka Nabeshima (Elsevier, 2005)
The mesocorticolimbic dopaminergic system plays an important role in the reinforcing effects of drugs of abuse, and the activity-dependent synaptic plasticity of the system is involved in drug dependence. A DNA microarray screening revealed that the expression levels of tissue plasminogen activator (tPA) mRNA in the nucleus accumbens of morphine- or methamphetamine-dependent rats were significantly increased compared with those in control animals. Since tPA plays a role in synaptic plasticity, we hypothesized that tPA may contribute to the development of drug dependence. Single and repeated morphine treatment as well as repeated methamphetamine treatment induced tPA mRNA expression in the nucleus accumbens, which was associated with an increase in the enzyme activity. Conditioned place preference induced by morphine was markedly reduced in mice with a targeted deletion of the tPA gene (tPA−/− mice), being accompanied by a loss of morphine-induced dopamine release. Similarly, methamphetamine-induced conditioned place preference and locomotor sensitization were reduced in tPA−/− mice. The defects of morphine-induced hyperlocomotion as well as methamphetamine-induced locomotor sensitization in tPA−/− mice were reversed by microinjection of exogenous tPA or plasmin into the nucleus accumbens. These results support our hypothesis that tPA plays a role in long-lasting neuronal changes related to drug dependence. Keywords:: dependence, methamphetamine, morphine, plasmin, tissue plasminogen activator